2007
DOI: 10.1523/jneurosci.3303-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Anxiety, Conditioned Fear, and Hippocampal Long-Term Potentiation in Transient Receptor Potential Vanilloid Type 1 Receptor-Deficient Mice

Abstract: The transient receptor potential vanilloid type 1 channel (TRPV1) (formerly called vanilloid receptor VR1) is known for its key role of functions in sensory nerves such as perception of inflammatory and thermal pain. Much less is known about the physiological significance of the TRPV1 expression in the brain. Here we demonstrate that TRPV1 knock-out mice (TRPV1-KO) show less anxiety-related behavior in the light-dark test and in the elevated plus maze than their wild-type littermates with no differences in loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
230
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(259 citation statements)
references
References 54 publications
17
230
2
5
Order By: Relevance
“…Moreover, Marsch et al (2007) showed that TRPV1 was involved in hippocampal synaptic plasticity using TRPV1 knock-out, and Gibson et al (2008) confirmed this finding by showing that capsaicin and capsazepine, respectively, induced and repressed hippocampal longterm depression (LTD). Nevertheless, Cavanaugh et al (2011) could not detect any TRPV1 expression in these two structures.…”
Section: Review Of Cavanaugh Et Almentioning
confidence: 79%
“…Moreover, Marsch et al (2007) showed that TRPV1 was involved in hippocampal synaptic plasticity using TRPV1 knock-out, and Gibson et al (2008) confirmed this finding by showing that capsaicin and capsazepine, respectively, induced and repressed hippocampal longterm depression (LTD). Nevertheless, Cavanaugh et al (2011) could not detect any TRPV1 expression in these two structures.…”
Section: Review Of Cavanaugh Et Almentioning
confidence: 79%
“…In contrast to the anxiolytic effect of TRPV2 in the PVN, however, TRPC5 seems to be anxiogenic in the amygdala, as TRPC5 −/− mice exhibit diminished innate fear in tests for general and social anxiety (Riccio et al, 2009). Likewise, TRPV1 knockout mice show decreased anxiety-like behavior in the LDB and EPM, as well as reduced conditioned fear, suggesting that TRPV1 activity promotes anxiogenic behavior (Marsch et al, 2007). In summary, our in vivo and in vitro studies identified TRPV2 channels in the PVN of rats as mediators of OXTinduced anxiolysis.…”
Section: Discussionmentioning
confidence: 97%
“…The TRPV1 antagonist capsazepine reversed the decline in 5-HT excitation induced by high WIN55,2212-2 doses. Interestingly, TRPV1 is expressed in both DR and PFC (Liapi and Wood, 2005) and is implicated in anxiety, conditioned fear, and hippocampal long-term potentiation (Marsch et al, 2007) and in schizophrenia (Chahl, 2007), whose negative symptoms overlap with depression. Second, we consider the possible role of the putative CB 3 R or a non-CB 1 cannabinoid receptor possessing a lower affinity to WIN55,212-2 proposed to be present in glutamatergic terminals and thus in a position to inhibit the release of excitatory amino acids (Hajos and Freund, 2002).…”
Section: Discussionmentioning
confidence: 99%